Evaluation of Pot Technology Preservation Techniques for Tomato Fruit in East Arsi, Ethiopia - Awulachew, Melaku Tafese (International Journal For Research In Agricultural And Food Science, 2019)
The aim of this study was to extend the shelf life of tomato fruits using pot in pot technology. Exposure of tomato fruits to high temperatures during postharvest reduces their storage shelf life. Pot in pot technology differs from common air conditioning and refrigeration technologies in that it can provide effective cooling without the need for external energy source. Pot in pot technology has been found to be an efficient and economical means of reducing temperatures and increasing humidity in an enclosure where the humidity is comparatively low. Consequently, Pot in pot is a low cost technology for storage of fruits. Pot in pot reduced the inside storage temperature 18.19 oC, the fridge to 11.57oC while the average room temperature was 20.4 oC. The average inside storage relative humidity for pot in pot was 67.31%, fridge was 59.11% .while the average room relative humidity was 59.42 %. Highest pH value was recorded for tomatoes stored inside room temperature (4.71) followed by pot in pot (4.66), and least value was recorded for fridge storage method (4.43) on 12 days all at light red ripening stage. The total soluble solid(TSS) content of tomato stored at room temperature (1.02 oBrix) and inside fridge (1.01oBrix) was the same as tomatoes stored inside pot in pot (1.01oBrix) on 12 days of storage at light red ripening stage and the least TSS content was recorded inside fridge (1.01oBrix) after 19 days of storage. The total titrable acidity was highest on tomatoes stored inside pot in pot (0.12%) and fridge (0.15%) while minimum TTA was recorded for room temperature (0.14%) after 12 days all at ripening stage.